A periodic review integrated inventory model for buyer's unidentified protection interval demand distribution. Issue 1 (31st December 2016) - Tahami, Hesamoddin; Mirzazadeh, Abolfazl; Arshadi-khamseh, Alireza; Gholami-Qadikolaei, Aref
Abstract: Nowadays, considering inflation observed in most societies, it is important to investigate on effect of this phenomenon on inventory/production decisions. Consequently, the paper aims to study the influence of inflationary condition on a specific periodic review integrated vendor–buyer inventory system in the presence of vendor's imperfect manufacturing process. The lead time crashing cost is represented as a piecewise linear function of reduced lead time. In practice, the identification of the protection interval demand distribution of restricted data is a difficult task. As a result, this investigation assumes that the information about the protection interval demand for buyer is limited to its mean and standard deviation. Buyer's ordering cost can be reduced through further investment. For the discussed model, an effective solution procedure is developed to determine optimal policy. Theorems on conditional convexity and concavity of objective cost function in the decision variables of the respective inflationary integrated inventory system are shown and proved. A numerical example is presented to illustrate the results of the proposed model.